Gamma Rays and EMS induced polygenic variability in Cicer arietinum L. var. Pusa â€“ 212 - Anis, Aijaz A. Wani, Mohammad (Journal of Phytology, 2015)
Present study revealed the induced polygenic variability in chickpea var. Pusa-212 following treatments with gamma rays (150 Gy, 200 Gy, 300 Gy & 400 Gy), EMS (0.1, 0.2, 0.3 & 0.4%) and their combinations (200Gy + 0.2%, 300Gy + 0.2%, 200Gy + 0.3% & 300Gy + 0.3% EMS). A significant amount of genetic variability was induced for various quantitative traits in the treated populations as compared to control in the M2 generation. In M3 generation, the amount of genetic variability was low compared to M2. Mean values for various polygenic traits showed positive and negative shifts in M2, whereas, significant positive shifts were noticed for yield and yield contributing traits in M3 generation.Â  For days to flowering, plant height and days to maturity, heritability (h2) increased, whereas, genetic advance decreased from M2 to M3 generation in most of the selected treatments indicating non additive gene effects. However, in case of number of fertile branches per plant, pods per plant, seeds per pod, 100 seed weight and total plant yield, all the genetic parameters (GCV, h2 and GA) increased from M2 to M3 generation in the selected treatments with a few exeptions indicating additive gene effects and chances for further improvement of these traits in the advanced generations. The selection was effective in M2 as significant gains in mean values coupled with high heritability and genetic advance were achieved for yield and yield contributing traits in M3 generation.